The Economic Thought of George Orwell - Roback, Jennifer (American Economic Review, 1985)
Despite the volumes that have been written about George Orwell during this past year of 1984, virtually no one has commented on the economic assumptions implicit in his work. Yet understanding the economics in Orwell's vision of hell is necessary if we are to fully appreciate the horror of that vision. Orwell believed that socialism led to totalitarianism; indeed, that is the chief message of Orwell's 1949 classic. But he also believed that capitalism led to breadlines and poverty. This combination of beliefs led him to that profoundly disturbing view he described so vividly in 1984. But probably the most remarkable aspect of Orwell's economic thought is that he said so little explicitly on the subject. He wrote literally volumes of social and political commentary, with an economic worldview implicit in every line. Yet, explicit discussion of economics is limited to a few pages in 1984 and offhand comments scattered throughout his book reviews and essays. The statements that he did make suggest that his economic ideas were obviously influenced by Marxist theory, but were not revolutionary. That is, his views were quite conventional for his time. His views about technology are quite another matter. Orwell was not opposed to or in favor of technology per se. His primary concern was over who would control technology. Would new technologies be widely available for personal use or would they be centrally controlled? In this area Orwell was a decentralist, radical for his time and for ours.